STUDY ON THE EFFECTIVENESS OF THE USE OF ARTIFICIAL INTELLIGENCE (AI) ON STUDENT LEARNING OUTCOMES: KAJIAN EFEKTIFITAS PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) TERHADAP HASIL BELAJAR PESERTA DIDIK - Simarmata, Justin Eduardo; Aprianti, Iis; Atencia, Bryant Bennet D.; Nahak, Kristofel Bere; Purnomo, Miko (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2024)
The development of information technology, particularly Artificial Intelligence (AI), has opened new opportunities in the field of education, including the teaching of Computer English courses at the University of Timor. This study aims to examine the effectiveness of using AI, particularly ChatGPT, as a learning assistant in improving student learning outcomes. The research method used is a quasi-experimental design, involving 30 students. Data were collected through pretest and posttest assessments, and subsequently analyzed using descriptive and inferential statistics, including the t-test. The results indicate that the implementation of AI has a significant impact on improving student learning outcomes in three evaluation aspects: writing about types of computers, making comparisons, and constructing comparative sentences. The t-test analysis shows that all differences between pretest and posttest scores are significant (p < 0.05). Furthermore, the use of AI also enhances the consistency of student scores, as reflected in the improvement of the minimum, average, and maximum scores in each evaluation section. In conclusion, the implementation of AI, such as ChatGPT, has been proven effective in supporting a more personalized, interactive, and adaptive learning process. This study recommends further development of AI usage in education to create innovative learning that is relevant to the needs of the digital era.